2019
DOI: 10.4046/trd.2018.0064
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Noninvasive Ventilation Use in Korean Intensive Care Units: A Prospective Multicenter Observational Study

Abstract: Background Data on noninvasive ventilation (NIV) use in intensive care units (ICUs) are very limited in South Korea. Methods A prospective observational study was performed in 20 ICUs of university-affiliated hospitals from June 2017 to February 2018. Adult patients (age>18 years) who were admitted to the ICU and received NIV treatment for acute respiratory failure were included. Results A total of 156 patients treated with NIV were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…However, in China today, pulmonary TB is rarely considered as a primary cause of respiratory distress. Despite this, pulmonary TB with respiratory failure is associated with high mortality (9).…”
Section: Introductionmentioning
confidence: 99%
“…However, in China today, pulmonary TB is rarely considered as a primary cause of respiratory distress. Despite this, pulmonary TB with respiratory failure is associated with high mortality (9).…”
Section: Introductionmentioning
confidence: 99%
“…Adult patients (aged > 18 years) who were admitted to these ICUs and received NIV treatment for acute respiratory failure were prospectively included. This data was one part of a nationwide data collection study on NIV in Korean ICUs [ 12 ]. The indications for NIV included the following: (1) acute hypercapnic respiratory failure, which was designated as respiratory failure occurring in a patient with chronic lung disease (obstructive or restrictive) and, (2) de novo respiratory failure, typically indicating respiratory failure in patients without chronic respiratory disease, primarily found in those with hypoxemic respiratory failure (e.g., pneumonia, postoperative respiratory failure, sepsis, or acute respiratory distress syndrome) [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the VVO group, noninvasive ventilation was more frequently used than in the O or VO groups. This trend likely reflects Korean cultural attitudes favoring the avoidance of invasive treatments for older patients [ 36 , 37 ]. These observations are consistent with the findings of several other studies that have reported similar treatment choice patterns for older patients in other cultural contexts [ 10 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%